THE CHORAL OUTLINE IN THE OPERA “ALEXANDRU LĂPUŞNEANU” BY GHEORGHE MUSTEA - Luminiţa GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
The music of Gheorghe Mustea displays a heterogeneous style, richly inspired by the compositional manner of the great composers of this genre (M. Mussorgsky, George Enescu), with elements of folk origin, of a special charm and richness. The most diverse sources present him to us in just as diverse creative states, in which the stylistic suggestions derive mainly from the Russian opera, namely “Boris Godunov” by M. Mussorgsky (through the grandeur in displaying the crowd scenes) – or from the Romanian folklore (by using the tonal-modal alternance, the intense chromatization of the music, the presence of local color touches, or the infusion of liveliness transposed into both rhythmic and intonational musical patterns). The composer has used elements of folkloric style in cult traditional musical forms, thus creating music pages of a strong national legitimacy. The characteristic of this opera that really stands out, in particular, is the impressive number of choral scenes. They are largely developed in this opera, in addition to the fact that they integrate the general atmosphere of the action, rather than outlining various personalities or feelings. When writing the choral score, the composer uses the sound calligraphy of folklore (particularly through melismas, appoggiaturas, glissandos, etc.), as well as rhythmic patterns specific to folk music. In dealing with the crowd scenes, the composer employs the entire sound potential provided by the choral voice parts, especially in the moments of climax and synthesis.